Aid for agriculture and rural development in the global south: A changing landscape with new players and challenges - Admos Chimhowu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper analyses the way aid for agriculture and rural development in the global south has changed over time. It finds three key shifts. First, a change in funding priority that has seen aid commitments move to the social sectors. Second is a shift in priority within agriculture and rural development from the productive sector towards support for policy development and administrative capacity strengthening. Third is the emergence and rise in commitments from non-traditional bilateral donors, private sector foundations and venture capital finance. The paper argues that these 'new' actors, often working outside the Development Aid Committee and other global official development assistance frameworks, have introduced alternative aid channels that not only complement but also reshape aid relationships between the traditional donors and the global south. It suggests further research to understand the impact of these new ways of financing development.
Keywords: F35; O13; O19; Q13; Q18; 330; aid agriculture; rural development; high-impact investments; venture philanthropy; Ländliche Entwicklung; Entwicklungshilfe; Entwicklungsländer